2018
DOI: 10.1155/2018/3158086
|View full text |Cite
|
Sign up to set email alerts
|

Using Pretreatment of Carbon Monoxide Combined with Chlorine Dioxide and Lactic Acid to Maintain Quality of Vacuum-Packaged Fresh Beef

Abstract: Due to microbial growth, beef easily gets corrupt in retail conditions, and the color and quality of the meat will be deteriorated. Therefore, hurdle technology, namely, pretreatment of carbon monoxide (CO), chlorine dioxide, and lactic acid, is used for vacuum-packaged beef to decontaminate beef and increase its quality stability. Beef was pretreated with 100% CO (C1), 100% CO and 50 mg/L chlorine dioxide (C2), and 100% CO and 50 mg/L chlorine dioxide and 30 g/L lactic acid (C3). The untreated samples were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…It is crucial to develop antibacterial agents that effectively develop antibacterial agents that efficiently block the development of spoilage or pathogenic bacteria without changing the taste or chemistry of the food. In meat factories, conventional antibacterial sanitizers use lactic acid spray-washing on beef carcasses at low temperatures [ 8 ]. Samelis et al [ 9 ] and Deumier [ 10 ] both demonstrated that although lactic acid (2–5%) significantly reduced surface contamination and extended the shelf-life of meat, a high concentration (>1%) could negatively affect the quality of meat.…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial to develop antibacterial agents that effectively develop antibacterial agents that efficiently block the development of spoilage or pathogenic bacteria without changing the taste or chemistry of the food. In meat factories, conventional antibacterial sanitizers use lactic acid spray-washing on beef carcasses at low temperatures [ 8 ]. Samelis et al [ 9 ] and Deumier [ 10 ] both demonstrated that although lactic acid (2–5%) significantly reduced surface contamination and extended the shelf-life of meat, a high concentration (>1%) could negatively affect the quality of meat.…”
Section: Introductionmentioning
confidence: 99%
“…The AOAC (1995) 14 technique was used for measuring pH. To sum up, a digital pH metre (make: Metrohm, Switzerland; model: 780) was used to record the pH after 10 g of TSM and 50 ml of distilled water were homogenised in a laboratory blender (POLYTRON, PT 300) for one min 15 .…”
Section: Phmentioning
confidence: 99%
“…According to a report by Zhou et al (2023), it has been suggested that a decrease in lactic acid bacteria during the fermentation process of Chinese sausages may be attributed to two factors. These factors include the apoptosis of bacteria and a reduction of the pH level, which ultimately reaches a certain threshold (Lyu et al, 2018). In addition, packaged processed foods can be classified based on pH into low acidic foods (pH above 5.2), medium acidic foods (pH 5.2-4.6), acidic foods (pH 4.6-4.0) (Lin et al, 2023), and high acidic foods (pH below 4.0).…”
Section: Effect Of Different Additives On the Tpc Of Chinese Sausages...mentioning
confidence: 99%
“…Moreover, lipid oxidation is associated with discoloration, poor shelf life, loss of nutritional value, off-flavor development (significant deterioration of quality, flavor, and taste), and meat product drips, making it an area of critical concern for those in the meat industry (Amoli et al, 2021;Domínguez et al, 2018;Faustman et al, 2022;Hadidi et al, 2022) Apart from the oxidation degradation of lipids in muscle tissues, various substances prone to oxidative degradation, such as unsaturated fatty acids, hemoglobin pigments, metal catalysts, and oxidants, can catalyze such chemical reactions (Cunha et al, 2018;de Carvalho et al, 2020;Domínguez et al, 2018Domínguez et al, , 2019Gagaoua et al, 2023;Manessis et al, 2020). It is worth noting that the issue at hand occurs with a frequency that is second only to cases of microbial spoilage (Lyu et al, 2018;Mahmud et al, 2023;Manessis et al, 2020). Therefore, it is crucial to implement effective measures to minimize the risk of lipid oxidation and maintain the quality of meat products throughout their production and storage cycle.…”
mentioning
confidence: 99%